Preferred techniques for forest mushrooms cooking by residents of contaminated areas of the Bryansk region in the remote period after the Chernobyl accident - K. V. Varfolomeeva; S. A. Zelentsova; V. S. Repin (Радиационная гигиена)
The  article  presents  results  of  the  analysis  of  questionnaire  survey  data  on  preferences  in  the  choice  of  cooking methods of different types of forest mushrooms by residents of the most contaminated south-western  districts  of  the  Bryansk  region  in  the  remote  period  after  the  Chernobyl  accident.  In  the  period  from  2019  to 2022, the employees of Federal Budgetary Institution of Science «Saint-Petersburg Research Institute of  Radiation Hygiene after Professor P.V. Ramzaev» conducted a face-to-face questionnaire survey of the adult  population.  In  addition  to  general  questions  about  the  respondent,  the  questionnaires  included  questions  about the species composition of the mushroom basket, the volume and proportion of consumption of each type  of mushroom by the respondent and his family members (both in the current and last year), as well as methods  of culinary processing of the mushrooms consumed. Based on the analysis of individual survey data, a group  of 1 311 respondents, whose diet included various types of mushrooms, was selected. Analysis of the survey  results showes that respondents prefer to process a large proportion of freshly picked forest mushrooms (59%)  for  long-term  storage  (pickling,  freezing,  drying,  salting,  etc.);  41%  of  mushrooms  are  consumed  immediately. The most popular pretreatments of freshly picked mushrooms are washing and boiling (34 and 26%,  respectively). When freezing, pickling and pickling up to 97% of respondents carry out pre-treatment (rinsing,  soaking and / or boiling) of freshly picked mushrooms. Less popular methods of the mushroom preparation  (from 2 to 4%) are pickling, drying and frying of fresh mushrooms with their subsequent preservation. Thus,  the majority of respondents actively use various types of culinary processing with the use of preliminary stages  of technological processing in the form of rinsing, soaking and (or) boiling. The use of the above methods of  pre-cooking of freshly harvested mushrooms leads to a decrease in the  137Cs content in the consumed product.